The role of the game element in the introductory-phonetic course in the study of foreign languages - Sokolova G. A. (Humanitarian, 2018)
this article discusses some aspects of teaching a foreign language at initial stages, the importance of using the game element when working on the introductory-phonetic course is emphasized.
Keywords: игра; произношение; иностранный язык; звук; родной язык; скороговорки; foreign language; game; pronunciation; вводно-фонетический курс; гимнастика речевого аппарата; sound; introductory-phonetic course; native language; gymnastics of the speech apparatus; tongue twisters